Predictors of success in the breeding soundness evaluation and infertility in bulls - Diaz Miranda, Edgar Andres (2022)
Bull fertility is critical for the profitability and sustainability of the cattle industry. To date, the Breeding soundness evaluation (BSE) is the best methodology to estimate the reproductive potential of future bulls. However, the guidelines for the BSE differ between practitioners and societies, perhaps due to a lack in research in this area. Therefore, our first study hypothesized that by the implementation and use of strict BSE guidelines the number of approved Nellore bulls and their reproductive quality would increase overtime. Furthermore, our second study hypothesized that bulls born early in the calving season are more likely to be approved in their first BSE when compared to males calved later. To evaluate these two hypotheses, records of 20 years and 46,566 BSE were used in two separate analyses including a multivariate logistic regression to measure the effect of the year and farm, and to predict the probability of approval in Nellore young bulls at their first BSE according to their dams calving date. Bulls were classified as approved (satisfactory potential breeders and qualified for natural breeding service) and not approved (deferred and unsatisfactory potential breeders). Overall, there was no improvement in the percentage of approved bulls. However, there was an increase in the number of bulls approved in the first BSE and an increase in the percentage of bulls classified as satisfactory potential breeders (P-value <0.05), which means that the quality of the bulls improved over time. On the other hand, it was demonstrated that the calving date affected the probability of approval at the first BSE. Hence, bulls born on day 0 of the calving season had 1.26 more chances to be approved at the first BSE than bulls born 21 days later. In our studies, 53% of the bulls were not approved due to poor sperm quality, specifically abnormal sperm morphology. Bull ejaculates with the aplastic midpiece defect (AMD) have poor motility and fertility and it’s related to have a putative genetic origin. Therefore, our third study aimed to understand the origin and factors contributing to the abnormal sperm production of the AMD in Dairy Gyr bulls. Six Dairy Gyr Bulls (three control bulls and three bulls with AMD) obtained from the same farm and management were castrated to conduct a sperm morphofunctional and proteomic study and evaluate the redox state of reproductive tissues. The morphological analysis demonstrated that the AMD is a consequence of defective spermiogenesis. Control bulls also produced a high percentage of AMD but have an effective mechanism of removal of the defective sperm prior to epididymal transit. This mechanism generates mild oxidative stress in the testis and caput of the epididymis (measured as MDA and CAT; P-value <0.05); however, the redox state was reestablished in the corpus and cauda of the epididymis. Furthermore, qualitative and quantitative proteomic analysis showed that the sperm maturation of the bulls with the AMD should be deficient once they had differences in protein expression and a poor enrichment of critical pathways for sperm fertility. Finally, our last study hypothesized that binder of sperm (BSP) proteins could be used as a potential biomarker of defective sperm. Therefore, we characterized the binding properties and abundance of the BSP proteins after discontinuous gradient centrifugation and found that; in the supernatant fractions, there was an increase of BSP proteins abundance when compared to the sperm pellet fractions (P- value <0.05). In the sperm pellet fractions, BSP1 and BSP3 bound predominately to the acrosomal region of the sperm head, whereas BSP5 had a high affinity for the midpiece. Furthermore, high BSP proteins abundance was found to be correlated with acrosome and membrane damage induced by permeabilization. Therefore, the abundance of BSP proteins could be used as biomarker of defective sperm or sperm with compromise function. Our results allowed us to complement the knowledge on bull fertility, from the basic but functionally BSE to biomarkers for defective sperm specially on Bos indicus cattle. Keywords: Bull fertility. Sperm morphology. BSPs. Biomarkers.